Waste Not, Want Not : The Efficiency of Health Expenditure in Emerging and Developing Economies - Grigoli, Francesco (IMF Working Papers; Working Paper, 2013)
Public health spending is low in emerging and developing economies relative to advanced economies and health outputs and outcomes need to be substantially improved. Simply increasing public expenditure in the health sector, however, may not significantly affect health outcomes if the efficiency of this spending is low. This paper quantifies the inefficiency of public health expenditure and the associated potential gains for emerging and developing economies using a stochastic frontier model that controls for the socioeconomic determinants of health, and provides country-specific estimates. The results suggest that African economies have the lowest efficiency. At current spending levels, they could boost life expectancy up to about five years if they followed best practices.